A Fuzzy Model for Ni-Cd Batteries - Mohammad Sarvi; Masoud Safari (Institute of Advanced Engineering and Science, 2013)
The batteries models found in the literature are based mainly on mathematical descriptions of physical, chemical, and electrochemical properties which are difficult to determine. This paper presents new fuzzy based model for Nickel Cadmium (Ni-Cd) batteries. The main advantage of the proposed models is that, the proposed model is able to predict battery output voltage without knowledge of numerous factors. Inputs of the proposed model are battery current and state of charge while battery voltage is selected as the output. To check the accuracy of the proposed models, simulations results are compared with the measured battery data at different charge current as well as many other battery models for a 7Ah, size F, Ni-Cd battery. Simulated shows good agreements with measured data. The advantage of fuzzy model is that for modeling by fuzzy method experimental data isn’t needed. The proposed models can apply for modeling of other batteries types.DOI: http://dx.doi.org/10.11591/ij-ai.v2i2.1784